Experimental study of thaw settlement and internal structural changes in frozen soil during the thawing process - Chunguang Xu; Ze Zhang; Yaojun Zhao; Doudou Jin; Qihao Yu; Xiangxi Meng (Case Studies in Construction Materials)
Global warming can cause surface temperatures to rise, which can trigger permafrost degradation and severe soil erosion. This erosion can contribute to the degradation of water and soil resources and threaten the stability of the terrestrial ecosystem of the cryosphere, which can also contribute to geological tectonic changes in cold regions. However, there is limited research on the changes in horizontal settlement that occurs during permafrost thawing. To study the internal settlement of permafrost after thawing, four types of soilice mixtures were thawed and analysed indoors to quantitatively describe the internal settlement process and moisture conditions in thawing permafrost and to determine the variation in permafrost thawing and settlement processes. The results indicated that there were variations in the packing density of the soil–ice mixtures according to the soil type. Additionally, the packing density exhibited a favourable correlation with the water content, and the following size relationship for the packing density of the different soil types at the same water content could be established: ST (sand) > HB (silty loam) > SL (sandy loam) > YC (silty clay). The soil types exhibited varying surface soil coefficients of variation (Cv), with sample HB yielding the highest Cv value of 10.15 % and sample SL exhibiting the lowest Cv value of 5.85 %. Cv gradually decreased with increasing sample depth, and the Cv in the deepest horizon reached approximately 1.58 %. There was a significant difference in the amount of surface settlement in the vertical direction among the different samples (P < 0.05). There was no significant difference in the settlement amount of the samples at 8 cm (P > 0.05). The residual thickness of the soil horizon in the samples tended to decrease with increasing soil horizon depth. In this study, the settlement deformation of the soil horizon in the freeze–thaw process along the horizontal and vertical directions was examined, which could provide a reference for the regulation of the evolution of the geological structure during permafrost degradation and theoretical guidance for studying engineering instability in cold regions.